Klasterisasi Data Karyawan Berdasarkan Penilaian Kinerja Menggunakan Metode K-Medoid - Jodi Laksana Putra; Indra Kanedi; Abdussalam Al Akbar (UNIVED Press, 2025)
Clustering Employee Data Based on Performance Appraisals Using the K-Medoid Method at the Regional Government Office of Central Bengkulu Regency can help employees to group employee performance data and can be used as a consideration to determine the results of employee performance evaluations each year. Grouping employee data based on the results of performance appraisals that have been carried out, namely the value of employee work targets (SKP) and work behavior values. The results of clustering on employee performance appraisal data, obtained 2 groups or clusters, namely high clusters (Cluster I) and low clusters (Cluster II). Clustering employee data based on performance appraisals using the k-medoid method at the Regional Government Office of Central Bengkulu Regency is made using the Visual Basic .Net programming language. Based on the tests that have been carried out, the functional of the application has run well and the application can help the Central Bengkulu Regency Regional Government Office in knowing employee performance based on 2 groups, namely high clusters and low clusters